Quality seed production of ridge gourd in hot-arid region - Kumar, Pawan; Choudhary, M. K.; Choudhary, B. R.; Rane, Jagadish (Indian Horticulture, 2025)
The arid region holds significant potential for cucurbit cultivation, offering both economic and nutritional benefits. The availability of land provides a valuable opportunity for producing high-quality cucurbit seeds, which is continuously in demand. The ridge gourd variety Thar Karni, known for its climate resilience, is particularly well-suited for arid regions and presents a promising opportunity for quality seed production. Seed production of ridge gourd can generate a net income of ₹1.80-2.0 lakh per ha. Moreover, seed production technology also enhances environmental sustainability by reducing the carbon footprint associated with long-distance seed procurement. It promotes sustainable farming practices and empowers local farmers, contributing to resilience and growth in the agricultural sector.